Technological Innovation in Anti-Bullying Education: A Systematic Review Based on Prisma - Vicky Dwi Wicaksono; Ika Rahmawati (Jurnal Kiprah Pendidikan, 2026)
This systematic review aims to identify the most effective types of technology applied in the context of anti-bullying education over the past ten years. Using the PRISMA approach and thematic synthesis, eight scientific articles were analyzed to evaluate the effectiveness of various forms of technological innovation, including educational games, mobile applications, interactive multimedia, and artificial intelligence (AI). The primary focus of this research is on how these technologies can enhance students' understanding, empathy, engagement, and intervention capabilities regarding bullying cases in school environments, particularly in elementary and secondary education settings. The findings indicate that gamification-based and interactive multimedia technologies are the most effective approaches in enhancing students' conceptual understanding, motivation, and prosocial attitudes. Educational games such as interactive e-books and digital simulations demonstrate significant improvements in students' social competencies and awareness of bullying issues. On the other hand, mobile applications and AI have high functional potential, but their effectiveness depends on participatory design, cultural sensitivity, and guarantees regarding user ethics and privacy.  Therefore, the integration of technology in anti-bullying education must be carried out strategically, based on educational psychology theories such as Social Emotional Learning and Self-Determination Theory, and involve the active participation of the school community. This research provides conceptual and practical contributions in designing technology-based policies and intervention programs oriented towards student well-being.